Exomeres and supermeres: Monolithic or diverse?. Issue 6 (3rd June 2022) - Tosar, Juan Pablo; Cayota, Alfonso; Witwer, Kenneth
Abstract: Extracellular vesicles (EVs), including exosomes and microvesicles, are far from being the only RNA‐containing extracellular particles (EPs). Recently, new 35‐nm‐sized EPs were discovered by asymmetric‐flow field‐flow fractionation and termed 'exomeres'. Purification of exomeres was later performed by differential ultracentrifugation as well. More recently, the supernatant of the high‐speed ultracentrifugation used to collect exomeres was further centrifuged to collect a new class of EP, termed 'supermeres'. Supermeres contain high quantities of extracellular RNA and are enriched in miR‐1246. They are also replete in disease biomarkers and can induce metabolic and adaptive changes in recipient cells. Here, we reanalysed proteomic and transcriptomic data obtained in this exciting study to obtain further insights into the molecular composition of exomeres and supermeres. We found that the top‐ranking RNAs in supermeres correspond to the footprints of extracellular protein complexes. These complexes protect fragments of the small nuclear RNA U2 and the 28S rRNA from extracellular ribonucleases (exRNases). We suggest that intracellular nanoparticles such as the U2 ribonucleoprotein, ribosomes and LGALS3BP ring‐like decamers are released into the extracellular space. These heterogeneous EPs might be further processed by exRNases and co‐isolate by ultracentrifugation with other components of exomeres and supermeres. We look forward to continuing progress in defining exRNA carriers, bridging process definitions with molecular composition and function.